The Role of Human Resources Development Management in Improving Creative Entrepreneurs at Overloops Photography, Yogyakarta, Indonesia - Gustrin Oktaviayu Cendhikalistya; Muhammad Said (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study are to determine: 1) the role of management in the development of creative entrepreneurship; 2) Human resource management strategy for Overloops as creative entrepreneurs; 3) Overloops’ strategy to emerge from the pandemic era and increase its capacity. This study used a qualitative method with SWOT analysis. The respondents were business owners, managers, and five employees. The results show that: 1) Management play very important role in the development of Overloops; 2) the development strategy obtained from SWOT analysis is in quadrant III. This strategy is carried out by Overloops by leaving conventional photography and switching to futuristic photography; 3) Overloops' strategy for post-pandemic stabilization are obtaining passive income and editing abroad content creator’s videos.